Determinan on Underpricing at The Initial Public Offering: Evidence Indonesia Stock Exchange - Dirvi Surya Abbas; Abdul Rauf; Imam Hidayat; Djenny Sasmita (Quantitative Economics and Management Studies, 2022)
The purpose of this study is to see how company size, earnings per share, profitability, financial leverage, and underwriter reputation affect underpricing during the initial public offering of companies listed on the Indonesia Stock Exchange (IDX). This study's object was selected utilizing a purposive sample approach with numerous provisions. Non-banking firms that conducted initial public offerings (IPOs) on the Indonesia Stock Exchange (IDX) between 2015 and 2019 were researched. Ninety-eight non-banking firms were collected as study samples from a total of 141. This is due to the fact that there are six banking businesses, sixty-two companies do not meet the requirements for inclusion in this study data, and thirteen companies do not exhibit underpricing. Two firms were relisted and delisted. Based on the findings of data analysis research, low earnings per share will also make investors not interested in buying shares of the company. So the company's level of uncertainty will increase. Underwriters also know more and more complete information about the market so that issuers are needed to determine primary market prices and investors to consider investing in the capital market. Meanwhile, the level of underpricing cannot be measured by the level of ROA generated by a company and the distrust of investors towards the financial statements produced by companies that conduct IPOs. DER cannot be used as a benchmark in considering the initial return expected by investors based on the findings of data analysis research. the author assumes investors' incompetence in analyzing a company's performance and relies solely on the stock price offered. The phenomenon of stock price underpricing caused by limited information about companies conducting initial public offerings (IPOs) motivates the authors to conduct this research to determine whether the information available in financial statements and information surrounding investors can be used as benchmarks in determining investment decisions. and calculate a stock's initial rate of return.